Towards novel constrained resorcarene-based platforms - Moore, Deborah (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
This thesis entitled "Towards Novel Constrained Resorcarene-Based Platforms" is divided into seven chapters. In Chapter 1, an introduction to resorcarene chemistry is given and a discussion of the various possible isomers is included. A review of further reactions that can be carried out on the resorcarene macrocycle is then given. This chapter also describes the aims of this project. In Chapter 2, work towards synthesising a novel resorcarene tail-to-tail dimer is described. Various synthetic methods were attempted, and the use of different catalysts and resorcinol derivatives in the initial resorcarene condensation reaction were investigated. Some success was had with a step-wise approach and this led to the isolation of novel resorcinol dimers. In Chapter 3, work on octamethylresorcarenes is presented. A study of the conditions that favour different conformers is presented and discussed which led to the development of a synthetic method selective for the chair conformer. Preliminary computational results to study the relative energies of the chair and boat conformers indicate that the chair isomer is the more thermodynamically favourable conformation. The post-condensation alkylation of novel OMRA macrocycles is also reported. In Chapter 4, a range of synthetic routes to upper and lower rim calix[4]arene aldehydes are reported. The subsequent reaction of these aldehyde derivatives with resorcinol is then discussed. In Chapter 5, the synthesis of a number of cavitand platforms, suitable for ligand attachment, is discussed. The synthesis of four novel cavitands and a preliminary study of their interaction with metal salts are also described. Finally, Chapter 6 details the proposed future work and Chapter 7 outlines the experimental procedures used in chapters 2, 3, 4 and 5, and presents the characterisation of the novel compounds prepared.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin